Qualifications and Skills Versus Future Competencies of Young Adult Poles - Magdalena Kawecka (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
In this article, we analyse the skills and competencies of young Polish adults in the context of a rapidly changing labour market. The research focuses on understanding how young adults, faced with technological progress, globalisation, and demographic changes, can adapt their skills to meet future job requirements. The study is based on data from the 2021 Human Capital Balance project. Using Principal Component Analysis (PCA) and the k-means clustering method, the aim is to identify key skills and competencies that will impact the future job prospects of young people. The importance of both technical professional skills and personal traits, such as communication, teamwork ability, creativity, and problem-solving approach, is highlighted in the work. In the context of the labour market, these skills are crucial for employees to perform tasks effectively and achieve professional success.